Academic entrepreneurial hybrids: Accounting and accountability in the case of MegaRide. Issue 5 (September 2022) - Spanò, Rosanna; Grossi, Giuseppe; Landi, Giovanni Catello
Abstract: The current paper focuses on how multiple values shape accounting and accountability practices in hybrid organizations. It concentrates on the complex domain of academic spin-offs, more fully described as hybrid knowledge-intensive organizations, aiming to understand how accounting and accountability practices can be constitutive of hybrid academic entrepreneurial logics and identities and how these, in turn, favor the development of accounting and accountability practices. The study employs a theoretically informed in-depth single case study of the academic spin-off MegaRide of the University of Naples Federico II (Italy) for the period January to May 2021. The findings show how, in MegaRide, hybrid academic entrepreneurial identities emerged at both the individual and organizational levels, leading to successful technology transfer, with an undeniable impact on the local context and society. Highlights: The paper addresses how multiple values shape accounting and accountability practices. The focus is on academic spin-offs as hybrid knowledge-intensive organizations. The study analyses the Italian academic spin-off MegaRide. It shows the interplay between accounting and accountability and hybrid academic entrepreneurial logics.